The Effects of Training in Music and Phonological Skills on Phonological Awareness in 4- to 6-Year-Old Children of Immigrant Families - Patscheke, Hanne; Degé, Franziska; Schwarzer, Gudrun (Frontiers in Psychology, 2016)
Children of immigrant families often have great difficulties with language and disadvantages in schooling. Phonological problems appear especially common. Thus, the aim of this study was to determine whether music training has a positive effect on the phonological awareness in these children. The effects of a music program were compared with an established phonological skills program and with a sports control group. Preschoolers of immigrants (19 boys, 20 girls) were randomly assigned to one of the three groups. All groups were trained three times a week for 20 minutes each, over a period of 14 weeks. Phonological awareness was tested prior to the beginning of the training and after the training phase. At the pretest, no differences between the groups were found regarding phonological awareness and control variables (age, gender, intelligence, socioeconomic status, language background, music experience). At the post-test, the music group and the phonological skills group showed a significant increase in phonological awareness of large phonological units. The effect size of the music training was larger compared to the phonological skills program. In contrast, the sports control group showed no significant increase in phonological awareness. The current results indicate that a music program could be used as an additional opportunity to promote phonological skills in children of immigrant families.